(untitled) (Interdisciplinary Studies Journal, 2025)
The present study investigated the relationship between proactivity and individual performance in a financial institution, considering the Baby Boomer, Generation X, and Generation Y cohorts, as well as male and female genders. The general objective was to understand how proactivity contributes to performance, addressing intergenerational and gender differences within the organizational environment. The methodology used was phenomenology, which enabled the analysis of the essence of meaning and the life-world of each individual. Accounts from 36 managers were analyzed, divided between those with higher and lower performance, using the software Meaning Constitution Analysis (MCA) to identify meaning units. The results demonstrated that proactivity is positively related to performance, although it is not a constant characteristic. High-performing individuals exhibited a higher frequency of proactive behaviors, characterized by greater initiative and responsibility for their deliverables, while the low-performing group often attributed their difficulties to external factors. Emotional factors such as anxiety and dissatisfaction were observed in both the high- and low-performing groups. It was concluded that proactivity is a dynamic element that may fluctuate depending on one’s life stage and environment. Pressure and other psychological factors were shown to impact both performance and the expression of proactive behaviors. The study emphasized the importance of questioning binary concepts in the literature, such as proactivity versus non-proactivity, proposing a broader and more contextual perspective. Moreover, the relevance of phenomenology as an investigative method was highlighted, offering genuine and detailed analyses that can be applied in future research. This work contributes to bridging theory and practice in the organizational environment, providing valuable insights for the development of tools aimed at improving individuals and companies.